Pengaruh Komunikasi Persuasif Kampanye Sosial Protokol Kesehatan, Motivasi, dan Pengetahuan Mahasiswa Terhadap Perilaku Mahasiswa dalam Melaksanakan Protokol Kesehatan - Teddy Dyatmika (President University, 2021)
The increase in positive confirmed cases in Indonesia is very worrying. One of the factors behind this positive confirmed number is the lack of public awareness in implementing health protocols. This study aims to determine what factors are dominant in changing people's behavior in carrying out health protocols. This research method uses quantitative methods using path regression analysis. The theory used is Elaboration Likelihood Model Theory. The population in this study were IAIN Pekalongan students totaling 11,653 students with a sample of 387 students with a stratified proportional random sampling technique. The results showed that the variable of persuasive communication through social campaigns (x1) did not have a significant influence either directly or indirectly on student behavior in implementing health protocols (z). The motivation variable (x2) has the most influential value in giving a direct influence on student behavior in carrying out health protocols (z) of 0.344 with a total effect of combining direct regression analysis with student attitudes (y) of 0, 403148. Knowledge students (x3) have a direct influence with the value of 0.131 and 0.253112 the total influence both directly and indirectly on student behavior in carrying out health protocols (z).